2001
DOI: 10.1016/s0738-3991(01)00111-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient education in Europe: united differences

Abstract: This issue of Patient Education and Counseling presents the state of the art of patient education in several European countries. It is based on papers presented at a meeting in Paris on the evolution and development of patient education in western, central and eastern Europe (May 1999). Also patient education in the US is presented in this issue. Patient education is defined as all the educational activities directed to patients, including aspects of therapeutic education, health education and clinical health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
11

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 23 publications
1
33
0
11
Order By: Relevance
“…Each chronic disease has explicit particular health education content, materials and strategies. [31] Similar to this line, Clinical Innovation and Governance, Family and Community Services, in 2014 reported that it is important when supporting people with a disability to note that there may be challenges in developing and maintaining communication and behavioral support on a daily basis. [32,33] This can be particularly evident when supporting people with complex communication and behavioral challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Each chronic disease has explicit particular health education content, materials and strategies. [31] Similar to this line, Clinical Innovation and Governance, Family and Community Services, in 2014 reported that it is important when supporting people with a disability to note that there may be challenges in developing and maintaining communication and behavioral support on a daily basis. [32,33] This can be particularly evident when supporting people with complex communication and behavioral challenges.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 There is a growing body of research evidence that illustrates the effectiveness of PE on enhancing patients' levels of empowerment, self-care behaviors, compliance with health care recommendations, satisfaction in health care settings, and quality of their life, and reducing their levels of anxiety. 3,4 Nurses are the largest group of the health care providers. They are at the forefront of patient care, and spend the most time with the patients and their family members.…”
Section: Introductionmentioning
confidence: 99%
“…Medical care providers are perceived to be responsible for providing reliable information concerning treatment after hospital discharge [5]. However, the study conducted among older patients discharged from an emergency department in Finland showed that only one in four patients and 40% of family members received no discharge education [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that as many as 20% of patients make major mistakes regarding discharge recommendations within the first three weeks [2]; moreover, 60-80% of patients do not follow recommendations regarding long-term treatment [3,4], which results in substantial health consequences. Medical care providers are responsible for adequate preparation of patients for discharge from the hospital [5]. Galvin et al [6] proposed an operational definition of readiness for hospital discharge that includes following attributes:…”
Section: Introductionmentioning
confidence: 99%